A Boy Asleep under the Sun: Versions of Sandro Penna - Penna, Sandro (punctum books, 2014)
Peter Valente's first encounter with Sandro Penna's poetry was while translating Pier Paolo Pasolini. At the time, Valente was reading a biography on Pasolini and learned of his close friendship with Penna. Pasolini insisted that among serious readers of poetry, Penna could not be ignored. Born in Perugia on June 12, 1906, Sandro Penna lived most of his life in Rome (he died there on January 21, 1977), except for a brief period in Milan where he worked as a library clerk. When Pasolini arrived in Rome in 1950 he sought out Penna to "show him around." He knew that Penna was in love with the same ragazzi who prowled the outskirts of Rome. In his poetry Penna clearly says who he is and how he feels. That is a rare enough quality these days. He moves away from the trappings of identity toward an honest expression of love. In Penna's work the beautiful is not conscious of itself and is therefore erotic: "Is not the beauty of those who are unaware of their beauty / more beautiful than those who are aware?"